Risk And Resilience in Digital Payment Adoption: Analyzing Consumer Behavior Through the UTAUT2 Framework in Pakistan - Muhammad Saadullah; Muhammad Naeem; Khush Bakhat Umer; Nabila Khan; Khawar Naheed; Muhammad Sheeraz; Nadeem Iqbal (Kurdish Studies, 2024)
This study investigates the factors affecting the adoption of digital payment systems in Pakistan with the lens unified theory of acceptance and use of technology 2 (UTAUT2) framework. Particularly this study aims to enhance the consumer's adoption of digital payment systems in Pakistan to increase their work performance. Also, the moderating role of technostress between behavioral intention and adoption of digital payment systems. Consumers of bank account holders specifically those who use mobile banking apps for making transactions in Pakistan are included in this study. A survey was conducted using a purposive sampling method for data collection. Partial least square equation modeling was employed to test the hypotheses with a sample of 386 mobile banking users. Furthermore, the Smart-Pls SEM technique was used in this study. In this study SEM technique was used for the Measurement model and Structural model, the measurement model was used for validity and reliability the structural model was used for testing the hypothesis. The results of the study found that performance expectancy, effort expectancy, facilitating conditions, and habit were major contributing factors to the consumer's adoption of digital payment systems in Pakistan. This research, conducted in Pakistan, investigates the UTAUT2 constructs on the BI of consumers to employ the adoption of digital payment systems. Technostress (TS) is introduced as a new variable within UTAUT2, functioning as a moderator. Notably, this is the first research, adoption of digital payment-related investigation conducted in Pakistan. The primary objective is to gain valuable insights into the banking industry, focusing specifically on consumer perceptions of the adoption of digital payment systems. This study is conducted on the comprehension of consumer behavior in the sphere of the adoption of digital payment systems by increasing awareness of the adoption of digital payment systems.
10.53555/ks.v12i2.3752
Keywords: 330; Performance expectancy; effort expectancy; Hedonic motivation; Adoption; Technostress; Habit